Concentrações séricas de progesterona, cortisol e tiroxina nas diferentes fases do ciclo estral de éguas - Rocha, Aline Silva [UNESP] (2013)
The aim of this study was to evaluate the variations on serum concentrations of cortisol, thyroxine and progesterone during the different phases of estrous cycle in mares, once in this specie there are some contradictory results concerning the concentration of these hormones on different periods. It was used 3 groups containing 6 mares in each, selected according to the phase of estrous cycle, determined by transrectal palpation and ultrasonographic exam of reproductive tract. Group 1 corresponds to anestrous mares, group 2 to diestro, group 3 to mares in estrous. It was performed blood collection daily, during followed 5 days to serum cortisol, progesterone and thyroxine dosage. The technique utilized to hormonal analysis was Radioimmunoassay with Coat-A-Count Kit (DPC- Diagnostic Products Corporation). We found an inverse relationship between progesterone and thyroxine during diestrus and it was observed higher concentration of cortisol levels during the estrous, however the occurence of ovulation was not prevented, suggesting the estrus is a stress factor for the animal, but in a mild form, which not interfere in the physiology of estrous cycle.